VD_FINDINFO HC / 2013 / 751 vom 18. November 2013 - VD Tribunal cantonal (2013)
ASSISTANCE JUDICIAIRE, DÉNUEMENT, PERSONNE À L'ASSISTANCE | 117 CPC (CH), 119 al. 6 CPC (CH), 319 let. b CPC (CH), 334 al. 1 CPC (CH)